1987
DOI: 10.1111/j.1524-4725.1987.tb00511.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pulsed Dye Laser: Its Use at 577 nm Wavelength

Abstract: The ability to increase laser-induced cutaneous blood vessel damage selectivity is dependent upon optimizing various intrinsic laser parameters. Varying the laser emission wavelength, pulse duration, and/or incident energy dosage allows the clinician potential improvement in the laser treatment of cutaneous small blood vessel processes such as port-wine hemangioma and telangiectasia. The pulsed dye laser at 577 nm and a pulse duration of 300 to 400 microseconds, incorporates desired laser parameters into its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Hypopigmentation occur ring after high energy doses was reported [6]. Some atrophy or slight skin depression has been reported but this is usu ally secondary to using high energy levels or applying repeated pulses of laser energy to the same spot [5,11,12]. In a single case, a hypertrophic scar was reported by Swinehart [13].…”
Section: Introductionmentioning
confidence: 92%
“…Hypopigmentation occur ring after high energy doses was reported [6]. Some atrophy or slight skin depression has been reported but this is usu ally secondary to using high energy levels or applying repeated pulses of laser energy to the same spot [5,11,12]. In a single case, a hypertrophic scar was reported by Swinehart [13].…”
Section: Introductionmentioning
confidence: 92%
“…Alternatively, hemody‐namic effects secondary to temperature changes in the skin might play an important role. Increased purpura thresholds have been demonstrated by cooling or heating human forearm skin prior to pulsed dye laser (577 nm) irradiation 3 . It was suggested that temperature induced vasomotor changes in blood flow influenced the nature of laser injury.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 15 years laser surgeons have experienced great success in the treatment of various benign cutaneous vascular lesions 1–4 . A major exception has been treatment of large (1 mm diameter) lower extremity telangiectases.…”
mentioning
confidence: 99%
“…However, this conservative approach has resulted in some residual pigmentation in all patients treated. Postinflammatory hyperpigmentation is a well recognized temporary side effect of cutaneous laser therapy to lower limbs 24–26 and some of the residual hyperpigmentation may be postinflammatory. This will generally fade spontaneously within 6 months.…”
Section: Discussionmentioning
confidence: 99%